Caries prevalence and COP rate in a school population of 12 years at the municipality of Copacabana 2013-2014 - Osorio, Jhon (Revista Estomatología, 2015)
Objective: Calculate the prevalence of caries and related factors in schoolchildren from 12 years in the municipality of Copacabana. Materials and methods: Cross sectional study, with a sample of 483 adolescents. Sociodemographic and practice in oral health variables were evaluated. Oral and evaluation DMF index according to the recommendations of the Ministry of Health was conducted. Univariate, bivariate analysis and OR calculation was performed. Results: 51% were men, 77.8% live in urban areas, 56.5% belong to stratum 2 and 63.6% belong to the contributory scheme. 41.8% change the toohtbrush every 30 days. 81.4% use dental floss with occasional use by 41.6% of students. Caries prevalence was higher in men with 53.6%, in rural área with 60.5%, in stratum 1 with 65.4% and subsidized scheme with 57.2%. The traditional DMF index was 1.26 and the modified was 0.99. The urban area of residence (OR 0.59 IC95% 0.38 to 0.92) and frequency upshift toohtbrush at 90 days (OR 0.54 IC95% 0.30 to 0.97) were identified as protective factors. Conclusion: Adolescents from the town of Copacabana present a lower prevalence in caries experience, as well as a traditional and modified DMF index lower than that reported by other studies. The importance of strengthening oral health habits such as flossing, control sugar intake and regular visits to the dentist is highlighted.